The Analysis of Verbal and Visual Signs on Samsung X BTS Advertisement - Saragi, Dian Megawati Agnes Putri (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
The objective of this study is to examine the verbal and visual signs found in the Samsung Galaxy S22 x BTS advertisement. The data from this study was downloaded through the official Samsung Indonesia Instagram post. The method for identifying and analyzing verbal and visual signs in advertising is based on Saussure theory (1959) which are signified and signifier. Barthes theory (1983) was utilized to analyze the meaning of verbal and visual signs and it was supported by Wierzbicka’s theory (1998) about analyzing about the meaning of colors. This analysis was conducted using a qualitative research method. The result of this research reveals all of the hidden meanings in Samsung advertisement collaborated with BTS. The signs of this study consist of the brand name, type of smartphone, and additional information about the features in the smartphone as well as the icon, color, and pose of the model in the advertisement.